Pengaruh Citra Merek, Ulasan Produk dan Digital Marketing terhadap Keputusan Pembelian Kosmetik Pixy di Kota Batam - Fadhilla Rizqa; Nora Pitri Nainggolan (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to assess the influence of brand image, product reviews, and digital marketing on purchasing decisions for Pixy cosmetics in Batam City. The utilized population consists of users who have used Pixy items, although the exact number is not yet known. The Lemeshow algorithm was used to count a total of 100 respondents using a purposive sampling strategy. Multiple linear regression models were used to test the data, along with data quality checks, classical assumption tests, influence tests, and hypothesis tests. The findings of multiple linear regression analysis show that brand image influences purchasing decisions by 59.9%. Product reviews influence 24.3% of purchasing choices. Digital marketing influences 40.9% of purchasing choices. Test results using the coefficient of determination (R2) show that brand image, product reviews and digital marketing can explain up to 70.9% of the variation in purchasing choices. Furthermore, the t test and F test show that brand image, product reviews, and digital marketing both individually and together have a good and big influence on the decision to purchase Pixy cosmetics in Batam City.